Social Responsibility In Reducing Poverty Involves Promoting Community Development - المحمدي شهد سلمان هلال (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Social responsibility is one of the most prominent modern tools that countries and institutions resort to in order to confront societal challenges, foremost among them the problem of poverty, which constitutes a real obstacle to achieving sustainable development. This research aims to study the role of social responsibility, whether at the individual or institutional level, in reducing poverty and promoting sustainable community development. The theoretical framework focuses on clarifying the three basic concepts: social responsibility, poverty, and sustainable development. It also addresses the interactive relationship between them and explains how social and economic initiatives implemented by institutions lead to positive long-term impacts on society. The research reviewed successful experiences of companies and institutions that implemented social programs with a tangible impact on reducing poverty, whether through financing small projects, training and qualifying youth, or improving the level of public services. The research used a questionnaire consisting of a personal values scale and a cultural beliefs scale, and the data were analyzed using descriptive statistics and correlation coefficients. The research concluded that promoting social responsibility is a strategic necessity for achieving sustainable community development, not a voluntary option, and requires close cooperation between governments, the private sector, and civil society. The research also recommended enacting laws that incentivize companies to invest in social development, with a focus on the most vulnerable groups.